2001
DOI: 10.1164/ajrccm.163.4.9907078
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution, Metabolism, and Excretion of a Respirable Antisense Oligonucleotide for Asthma

Abstract: EPI-2010 is a respirable antisense oligonucleotide (RASON), which selectively attenuates discordantly overexpressed adenosine A(1) receptors in allergic lung (Nature 1997;385:721). In the present study, aerosolized [(35)S]-labeled EPI-2010 (5 mg exposure; specific activity 0.055 Ci/mmol) was administered to normal rabbits by endotracheal tube to assess biodistribution, route of elimination, and potential cardiovascular toxicity. The animals were killed at 0, 6, 24, 48, and 72 h after inhalation of EPI-2010. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…In animals, ISS have been shown to be active when applied to the mucosae of the lung and eye as well as other sites (reviewed in reference 29). Studies of oligonucleotides administered to the pulmonary mucosa indicate that these molecules are predominantly retained by lung tissue, with only 7% of the administered dose detected in all others organs combined (1). The oligonucleotides have a reported half-life of 30 h in this tissue, with minimal detectable levels present at 72 h after administration (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animals, ISS have been shown to be active when applied to the mucosae of the lung and eye as well as other sites (reviewed in reference 29). Studies of oligonucleotides administered to the pulmonary mucosa indicate that these molecules are predominantly retained by lung tissue, with only 7% of the administered dose detected in all others organs combined (1). The oligonucleotides have a reported half-life of 30 h in this tissue, with minimal detectable levels present at 72 h after administration (1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of oligonucleotides administered to the pulmonary mucosa indicate that these molecules are predominantly retained by lung tissue, with only 7% of the administered dose detected in all others organs combined (1). The oligonucleotides have a reported half-life of 30 h in this tissue, with minimal detectable levels present at 72 h after administration (1). Additionally, in these reports, oligonucleotide doses of as much as 20 mg showed no toxicity (1).…”
Section: Discussionmentioning
confidence: 99%
“…The lung has a very large absorption surface area, at the same time, it is lined with surfactant, a cationic glycolipid at physiologic pH, which serves as a carrier to facilitate ASON uptake into lung cells. Ali et al reported that aerosolized ASON was mainly distributed in lung tissue other than in other organs including heart, liver and kidney, and had no toxic effects (18). But, by intravenous or intraperitoneal administration, ASON mainly localized in liver and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics properties following pulmonary delivery has been well characterized (Templin et al 2000;Ali et al 2001;Guimond et al 2008) and confers a significant advantage of AON over small molecule drugs. For example, orally-delivered Daxas/Daliresp has a bioavailabilty of 79% (David 2004) and with an elimination half-life of 14-18 h there is a greater opportunity for this drug to act upon PDE4 outside of the lung and for a long period of time.…”
Section: Pxs Tpi1100mentioning
confidence: 99%
“…Firstly, as PXS TPI1100 is administered via inhalation, it is delivered directly to the intended site of action of the lung (Ali et al 2001;Duan et al 2005;Gauvreau et al 2008;Guimond et al 2008) where the drug can enter target cells directly (Zhang et al 2004;Griesenbach et al 2006) thus potentially reducing total dose as compared to orally-available treatments. A further advantage of pulmonary administration of AON is that they are principally www.intechopen.com A Multi-Targeted Antisense Oligonucleoitde-Based Therapy Directed at Phosphodiesterases 4 and 7 for COPD 449 metabolized in the lung with very limited systemic delivery after inhalation (Templin et al 2000;Ali et al 2001;Guimond et al 2008) which leads to reduced systemic bioavailability of the drug. In comparison to Daxas/Daliresp, which is delivered orally and has a high level of bioavailability, the projected low systemic bioavailability of PXS TPI1100 may limit adverse events associated with PDE4 inhibitors, namely the gastrointestinal and neurological side effects.…”
Section: Challenges In Copd Clinical Studiesmentioning
confidence: 99%